Apocrine Sweat Gland Ductal Adenoma with Sebaceous Differentiation in a Dog. (18th December 2013) - Michishita, Masaki; Yasui, Junki; Nakahira, Rei; Yoshimura, Hisashi; Takahashi, Kimimasa
Abstract : A 7-year-old male, Border Collie, developed a firm mass, measuring approximately 1 cm in diameter, in the left buccal skin. Histologically, the mass was composed of ductal structures lined by bilayered luminal epithelial and basaloid tumor cells along with a few nests of sebaceous cells. Immunohistochemical staining revealed that the luminal epithelial tumor cells were positive for cytokeratin (CK, CAM5.2) and CK19 but not for CK14 or p63. In contrast, the basaloid tumor cells were positive for CK14, p63, and α SMA but not for CK19 or CAM5.2. CK8 expression was observed in both luminal epithelial and basaloid tumor cells. The tumor cells with sebaceous differentiation were positive for CK14 but not for the other markers. This is the first case of an apocrine sweat gland ductal adenoma with sebaceous differentiation occurring in the buccal skin of a dog.